2017
DOI: 10.1039/c7cp03995f
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically enhanced photocatalytic reduction of CO2 on N–Fe codoped BiVO4 under visible light irradiation

Abstract: A N and Fe codoped monoclinic BiVO (N-Fe-BVO) photocatalyst was prepared via a conventional sol-gel method and was evaluated for the photocatalytic reduction of CO with HO under visible-light irradiation (>400 nm). As revealed by the structural and photoelectric characterization, the doped N and Fe species can enter the lattice of BiVO and induce the codopant levels in the forbidden region of BiVO, which helps in increasing visible-light absorption, suppressing charge recombination and promoting charge migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…However, the photocatalytic performance would decline along with the excessive addition of Bi 2 O 3 , which might be aroused by the reduce of the specic surface area, and the excessive Bi 2 O 3 might act as the recombination core of electron-hole pairs during the reaction. 55,56 The photocatalytic stability of all composites and g-C 3 N 4 are shown in the Fig. S1, † the yield of CO keeps stable during three experimental runs, revealing that the performance of all composites and g-C 3 N 4 are stable during the reaction.…”
Section: Photocatalytic Activity Pl and Photoelectrochemicalmentioning
confidence: 92%
“…However, the photocatalytic performance would decline along with the excessive addition of Bi 2 O 3 , which might be aroused by the reduce of the specic surface area, and the excessive Bi 2 O 3 might act as the recombination core of electron-hole pairs during the reaction. 55,56 The photocatalytic stability of all composites and g-C 3 N 4 are shown in the Fig. S1, † the yield of CO keeps stable during three experimental runs, revealing that the performance of all composites and g-C 3 N 4 are stable during the reaction.…”
Section: Photocatalytic Activity Pl and Photoelectrochemicalmentioning
confidence: 92%
“…Light absorption, band structure and carrier dynamics can be adjusted by heteroatom doping, which further affects the catalytic performance. Metallic elements (e. g., Fe, Co, and noble elements) [25a,70] and non‐metallic elements (e. g., C, N, and I) [71] doping both have been widely reported. Doping could capture the electron/hole to inhibit the recombination or accelerate the charge migration process to the interface.…”
Section: Strategies For Optimizing Co2 Photoreduction Activitymentioning
confidence: 99%
“…In addition to single element doping, Cao et al. reported a N−Fe co‐doped monoclinic BiVO 4 with the reaction rate of 27 mmol h −1 g −1 and a corresponding quantum efficiency of 1.86% [25a] . The doped N and Fe species which entered the lattice of BiVO 4 could narrow band gap to expand light absorption range, suppress charge recombination as well as promote charge migration.…”
Section: Strategies For Optimizing Co2 Photoreduction Activitymentioning
confidence: 99%
“…Peng et al also demonstrated the photocatalytic activity of BiOV 4 for the selectiver eduction of CO 2 to methanol. [190] For instance, N-and Fe-doped BiVO 4 showed increased visible-light absorption and enhanced photoinduced carriers eparation efficiency.C ompared with pure or single-doped BiVO 4 ,N ÀFeÀ BiVO 4 exhibited substantially improved visible-light activity for CO 2 reduction, witht he highest quantum efficiency of 1.86 % for hydrocarbong eneration.B iVO 4 was also coupledw ith nanocrystalline SnO 2 to construct heterojunctions, and silicate bridgesw ere introduced between the interfaces of BiVO 4 and SnO 2 . [188] As shown in Figure layers with poor vanadium vacancies.…”
Section: Bivomentioning
confidence: 99%
“…Therefore, some strategies were used to restrain photocorrosion.T he same methodsu sed for improving the performance of BiOX photocatalytic materials,s uch as enhancing photoinduced carrier separation efficiency,h eterojunction construction, and element doping, were used to suppress charge recombination and promotec harge migration on BiVO 4 . [190] For instance, N-and Fe-doped BiVO 4 showed increased visible-light absorption and enhanced photoinduced carriers eparation efficiency.C ompared with pure or single-doped BiVO 4 ,N ÀFeÀ BiVO 4 exhibited substantially improved visible-light activity for CO 2 reduction, witht he highest quantum efficiency of 1.86 % for hydrocarbong eneration.B iVO 4 was also coupledw ith nanocrystalline SnO 2 to construct heterojunctions, and silicate bridgesw ere introduced between the interfaces of BiVO 4 and SnO 2 . [191] The composition-optimized SnO 2 /BiVO 4 nanocomposite exhibited exceptional visible-light photocatalytic activities for CO 2 -to-CH 4 conversion and 2,4-dichlorophenol degradation.…”
Section: Bivomentioning
confidence: 99%